2020
DOI: 10.1021/jacs.0c05264
|View full text |Cite
|
Sign up to set email alerts
|

Guest Transition Metals in Host Inorganic Nanocapsules: Single Sites, Discrete Electron Transfer, and Atomic Scale Structure

Abstract: Host–guest solution chemistry with a wide range of organic hosts is an important and established research area, while the use of inorganic hosts is a more nascent area of research. In the recent past in a few cases, Keplerate-type molybdenum oxide-based porous, spherical clusters, shorthand notation {Mo 132 }, have been used as hosts for organic guests. Here, we demonstrate the synthetically controlled encapsulation of first-row transition metals (M = Mn, Fe, and Co) within a Keplerate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 63 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…Within the POM framework it is feasible to incorporate heteroatom with strong covalent interactions. For example, the Keggin type POMs can strongly hold other metals, whereas in lacunary POMs the vacant sites can be filled by any other transition metal with appropriate size and charge. , The POM wheel or ball can accommodate certain transition metals inside the pocket that can act as a single site. Zhang et al showed that a Pt single atom could be stabilized in the polyoxometalate framework where Pt is coordinated to the oxygen of the phosphomolybdic acid (H 3 PMo 12 O 40 ) . The DFT optimized structure also revealed that Pt atoms indeed prefer to absorb on the PMA at the 4-fold hollow site with absorption energy of −5.72 eV.…”
Section: Single-atom Catalysts (Sacs): Strategies Toward Synthesis An...mentioning
confidence: 99%
“…Within the POM framework it is feasible to incorporate heteroatom with strong covalent interactions. For example, the Keggin type POMs can strongly hold other metals, whereas in lacunary POMs the vacant sites can be filled by any other transition metal with appropriate size and charge. , The POM wheel or ball can accommodate certain transition metals inside the pocket that can act as a single site. Zhang et al showed that a Pt single atom could be stabilized in the polyoxometalate framework where Pt is coordinated to the oxygen of the phosphomolybdic acid (H 3 PMo 12 O 40 ) . The DFT optimized structure also revealed that Pt atoms indeed prefer to absorb on the PMA at the 4-fold hollow site with absorption energy of −5.72 eV.…”
Section: Single-atom Catalysts (Sacs): Strategies Toward Synthesis An...mentioning
confidence: 99%
“…It is presumed that due to a larger ionic radius of the Sb III ion (Sb III = 76 pm > As III = 58 pm), more central space needs to be freed up for satisfying the growth of Sb III -oxo clusters, which is not achievable due to the confined area defined by the rigid P 8 W 48 . Therefore, the SbO 3 3– groups choose to reside in the corners, and the resulting structural patterns in Sb 4 and Sb 8 are reminiscent of those discovered in [(Se IV O) 4 P 8 W 48 O 184 ] and [(Sn II Cl) 8 P 8 W 48 O 184 ], respectively.…”
Section: Resultsmentioning
confidence: 90%
“…Unlike the well-studied nucleation of guest clusters in organic or hybrid hosts, research about pure inorganic host–guest systems is still in its primary stage. Thanks to the adjustable structures, rigid scaffolds, and nanosize effects, polyoxometalates (POMs) represent a unique class of anionic polynuclear metal-oxide clusters that are competent for being receptors in host–guest complexation. The 48-tungsto-8-phosphate [H 7 P 8 W 48 O 184 ] 33– (P 8 W 48 ) nanowheel, in particular, stands as a prevalent model for confinement of a suitable microenvironment in support of the growth of metal-oxo clusters. It is built from four hexa-vacant, Dawson-type [H 2 P 2 W 12 O 48 ] 12– (P 2 W 12 ) fragments looped by W–O–W linkages between capping tungsten addenda, exposing a circular area with a diameter of about 1 nm.…”
Section: Introductionmentioning
confidence: 99%
“…That said, polyoxometalates (POMs) are a versatile class of discrete, anionic metal–oxygen clusters that can engage in host–guest chemistry, while providing inherent advantages as receptors due to their tunable structures, oxygen-enriched surfaces, and rigid scaffolds, which allow for the capture of guests, ranging in size from a single metal ion to sub-nanometer clusters. This capture is driven by forces, including but not limited to, coordination recognitions …”
Section: Introductionmentioning
confidence: 99%